Incidence and characteristics of paediatric abusive head trauma in Taiwan, 2006–2015: a nationwide population-based study. Issue 4 (11th August 2020) - Chang, Yi-Ting; Chang, Hsin-Yi; Chen, Li-Wen; Lu, Tsung-Hsueh; Tsai, Hui-Ju; Chen, Yi-Wen; Chang, Yu-Chun; Feng, Jui-Ying
Abstract : Objectives: To examine the incidence rate and characteristics of paediatric abusive head trauma (PAHT) among children under age 5 years in Taiwan. Methods: The International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) was used to identify broad and narrow definitions of children aged under 5 years with PAHT from 2006 to 2015 in Taiwan using a representative national insurance research database. Medical resource utilisation was also analysed. Incidence rates per 100 000 person-years were calculated and presented with 95% CI. Joinpoint regression analysis was used to detect the changes in trends and calculate the annual percentage change in PAHT incidence over time. Results: From 2006 to 2015, 479 (narrow definition) and 538 (broad definition) PAHT cases were identified. Incidence rates of PAHT by narrow and broad definitions among children under 1 year of age (18.7/100 000 and 20.0/100 000) were nearly 10-fold or 20-fold higher than for children aged 1–2 (1.7/100 000 and 2.1/100 000) and 3–5 (0.9/100 000 and 1.2/100 000) years. The PAHT incidence significantly increased since 2012, with trends varying by age and gender. Our results suggest that over 40% of the children with PAHT experienced serious injury and nearly 13% were fatal cases. For 87% (n=57) of fatal cases, this was their first ever hospitalisation. The number of fatal cases among infants was fourfold higher than that of children aged 1–5 years. Conclusions: This study provides a robust national estimate of PAHT and identifies infants as the most vulnerable group for PAHT in Taiwan. Education to enhance healthcare profession's sensitivity and competence for the early identification and diagnosis of PAHT is critical.